ANALISIS PERAN OMBUDSMAN REPUBLIK INDONESIA PERIODE TAHUN 2016-2021 SEBAGAI PENGAWASAN PELAYANAN PUBLIK - Dwi Anggraeni Septianingtiyas Anggraeni Septianingtiyas Septianingtiyas; Sulistyowati - - (Journal of Politic and Government Studies, 2021)
This research was conducted with the aim of analyzing the role of the Indonesian Ombudsman by ensuring that all reports are followed up and the strength of the recommendations issued, by looking at the position of the Indonesian Ombudsman in Indonesia. This research uses Institutionalism theory. The research method used in this research is descriptive qualitative with interview data collection techniques and documentation. The data obtained were then analyzed using a triangulation model, namely comparing the results of interviews, observations and review of existing documentation. The results of this study include the first one related to the recommendation of the Ombudsman of the Republic of Indonesia, still more than 50% of the reported agencies did not implement the recommendations issued. Second, that of the total 14333 reports that were submitted, all received follow-up from the Indonesian Ombudsman without any delay or failure of the investigation. Third, about 67% of the public do not know what an Ombudsman is, this shows that the Ombudsman has not been fully maximized in obtaining all reports. Fourth, that agencies receive sanctions if they do not implement recommendations, namely social sanctions in the form of publication of cases and reported agencies in the mass media and political sanctions in the form of reports from the Indonesian Ombudsman to the DPR or the President to take firm action.